Padma's all American : tales, travels, and recipes from Taste the Nation and beyond - Lakshmi, Padma (Alfred A. Knopf, 2025)
"From the Top Chef host and award-winning cookbook author, a culinary anthology filled with 100 authentic recipes from ethnic communities across America and discovered while filming Taste the Nation"--